Current concepts on hemodynamic support and therapy in septic shock - Rocha,Leonardo Lima (2015)
ABSTRACTSevere sepsis and septic shock represent a major healthcare challenge. Much of the improvement in mortality associated with septic shock is related to early recognition combined with timely fluid resuscitation and adequate antibiotics administration. The main goals of septic shock resuscitation include intravascular replenishment, maintenance of adequate perfusion pressure and oxygen delivery to tissues. To achieve those goals, fluid responsiveness evaluation and complementary interventions - i.e. vasopressors, inotropes and blood transfusion - may be necessary. This article is a literature review of the available evidence on the initial hemodynamic support of the septic shock patients presenting to the emergency room or to the intensive care unit and the main interventions available to reach those targets, focusing on fluid and vasopressor therapy, blood transfusion and inotrope administration.